Candidate coethnicity, rural/urban divides, and partisanship in Africa. (July 2021) - Harding, Robin; Michelitch, Kristin
Why do some citizens in new democracies attach to parties while others do not? We investigate the determinants of partisanship in Africa by theorizing the role of parties' group mobilization tactics and testing our arguments alongside existing explanations from new democracies. First, using original data on candidate ethnicity, we evaluate a debate as to whether coethnicity with presidential and/or vice presidential candidates is associated with greater partisanship. Contrary to traditional wisdom, we find no continent-wide relationship—prominently studied cases (e.g. Kenya, Ghana) may be falsely overgeneralized. Second, we propose that partisanship is more likely among rural citizens. We find robust, continent-wide support for this relationship, which we show is partially driven by citizens' links to traditional authorities, who often act as opinion leaders and/or brokers for parties. As in other new democracies, partisanship is positively associated with experience with multiparty democracy, the electoral cycle, age, male gender, and education.